Application of critical intensity model during slide board skating - Piucco, T.; Dantas de Lucas, R. (Applied Physiology, Nutrition, and Metabolism, 2019)
Critical cadence (CC), critical power (CP), and the work above CP (W') were determined from linear and hyperbolic modelling during skating on a slide board, in 13 well-trained speed skaters. Three to 4 trials to exhaustion were used for the fitting. CC from the linear model was higher than the hyperbolic model (56.0 ± 4.8 vs 55.0 ± 4.5 push-offs/min, p = 0.01). No differences were found for CP and W' parameters from the models analyzed.